Quasi-Dimensional Modelling and Parametric Studies of a Heavy-Duty HCCI Engine - Sunil Kumar Pandey; Muralitharan N.; Ravikrishna R. V. (Journal of Combustion)
A quasi-dimensional modelling study is conducted for the first time for a heavy duty, diesel-fuelled, multicylinder engine operating in HCCI mode. This quasidimensional approach involves a zero-dimensional single-zone homogeneous charge compression ignition (HCCI) combustion model along with a one-dimensional treatment of the intake and exhaust systems. A skeletal chemical kinetic scheme for n-heptane was used in the simulations. Exhaust gas recirculation (EGR) and compression ratio (CR) were the two parameters that were altered in order to deal with the challenges of combustion phasing control and operating load range extension. Results from the HCCI mode simulations show good potential when compared to conventional diesel performance with respect to important performance parameters such as peak firing pressure, specific fuel consumption, peak pressure rise, and combustion noise. This study shows that HCCI combustion mode can be employed at part load of 25% varying the EGR rates between 0 and 60%.